The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/bec.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Pick a Card, Any Card: The Relationship Between Anxiety, Obsessive-Compulsive Symptoms and Decision-Making

Abstract: Specific deficits in decision-making have been demonstrated in patients with obsessive-compulsive disorder (OCD). The experience of anxious arousal in obsessive-compulsive (OC) patients has been posited to be responsible for disrupting the cognitive processes that lead to efficacious decision-making (Sachdev & Malhi, 2005). In spite of this, research has neglected to examine explicitly the effect of anxiety on the relationship between decision-making and OCD. The current study investigates whether decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In the present study, the heart of the analysis in hierarchical regressions (e.g., interaction) explained a trivial proportion of variance in the dependent variable (1–4%). Compared with the regression effects of similar studies, we found that one study used hierarchical regression to explore the relationship between anxiety and IGT (Leonello & Jones, 2016), and their range of regression effects ( R ‐squared values) is 0.04–0.06, which was similar to our study. Moreover, in other studies focusing on intelligence and IGT, their regression effects ( R ‐squared values) are 0.001–0.17 in Demaree et al (2010) while 0.004–0.202 in Webb et al (2014).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the heart of the analysis in hierarchical regressions (e.g., interaction) explained a trivial proportion of variance in the dependent variable (1–4%). Compared with the regression effects of similar studies, we found that one study used hierarchical regression to explore the relationship between anxiety and IGT (Leonello & Jones, 2016), and their range of regression effects ( R ‐squared values) is 0.04–0.06, which was similar to our study. Moreover, in other studies focusing on intelligence and IGT, their regression effects ( R ‐squared values) are 0.001–0.17 in Demaree et al (2010) while 0.004–0.202 in Webb et al (2014).…”
Section: Discussionsupporting
confidence: 85%